Mitochondrial characterisation of two Spanish populations from the Vera and Bejar valleys (Central Spain) - Sara Varano; Luca Gaspari; Flavio De Angelis; Giuseppina Scano; Irene Contini; Cristina Martínez-Labarga; Olga Rickards (Annals of Human Biology, 2018)
This survey reports the mitochondrial data of two Spanish populations living in the Vera and Bejar valleys, on the opposite slopes of the Sierra de Gredos (Central Spain), which crosses Spain east to west. The aim of the study was to characterise the mitochondrial genetic pool of the Vera and Bejar populations to investigate a putative mitogenetic differentiation between them, evidence that would support the role of the Sierra de Gredos as a genetic barrier in their micro-evolutionary histories. Blood samples of 137 people (66 from Vera and 71 from Bejar) were collected and mtDNA hypervariable regions I and II (HVR-I and HVR-II) were dissected along with several mtDNA-coding region SNPs. The main European mitochondrial lineages have been found both in Vera and in Bejar, together with the typical African haplogroups L (in Vera) and U6 (in Bejar). FST value and the 95% credible regions calculated for haplogroup frequencies do not reveal genetic differentiation among the populations. Vera and Bejar contain an expected mitochondrial variability within them, but they do not seem to be genetically different from each other, leading us to conclude that the Sierra de Gredos is not a significant genetic barrier in their maternal genetic history.